PEMANFAATAN POTENSI LOKAL UNTUK PEMBERDAYAAN EKONOMI IBU RUMAH TANGGA DI REJOSARI MELALUI PEPAYA MUSTOFA ANEKA RASA - Lestari; Syamda Arum Philosofi; Rina Rahayu; Nevi Cindia Cahayati (STKIP Subang, 2024)
Rejosari Village in Magetan Regency has abundant natural resource potential in the form of papaya, but its utilization is still limited. This community service program aims to empower housewives through the production and marketing of Papaya Mustofa Aneka Rasa as an effort to increase family income. The implementation method includes technical training, marketing strategies, and ongoing mentoring. The results showed that the women were able to produce innovative products with high quality, improve their entrepreneurial skills, and boost their income by 35% in six months. This article outlines the steps of the program and its positive impact on the household economy.